The Effect of Storytelling on English Maritime Students’ Reading Comprehension at Politeknik Pelayaran Malahayati - Yusrah; Neneng Sri Lestari; Yunita Sari Adelina (English Lecturers and Teachers Association (ELTA), 2025)
This study investigated the effectiveness of storytelling as an instructional strategy for improving students’ reading comprehension. A quasi-experimental design was employed, involving 32 students divided into a control group (n=14) and an experimental group (n=18). The control group was taught using conventional methods, while the experimental group received a storytelling-based intervention. Pre-test and post-test scores were analyzed to measure the impact of the teaching methods.The results showed a significant improvement in the experimental group’s reading comprehension. The mean score for the experimental group increased from 64.89 in the pre-test to 78.22 in the post-test, while the control group’s mean score only increased from 65.21 to 68.57. A paired t-test revealed that the experimental group’s improvement was statistically significant (t=6.72, p<0.01), whereas the control group’s improvement was not (t=1.85, p>0.05). An independent t-test comparing the post-test scores of the two groups confirmed a significant difference (t=4.29, p<0.01), with the experimental group outperforming the control group. The effect size (Cohen’s d=1.12) indicated a large impact of the storytelling intervention. These findings highlighted storytelling’s potential to enhance students’ reading comprehension by fostering engagement and deeper understanding of the material. The study underscores the importance of integrating innovative teaching strategies, such as storytelling, into educational practices to improve learning outcomes. Further research is recommended to explore its application across different subjects and educational levels. Keywords : storytelling, teaching strategy, reading comprehension